STRATEGI JEPANG DALAM MEMPERTAHANKAN DOMINASI EKSPOR ROBOT DI CHINA - Putri Atiqah Purnama Sari; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
books, journals, newspapers, the internet, and previous research has nothingto do with the title. Perspectives and levels of analysis used in this study is that thestate as the main actor. By using a liberal perspective, the theory of competitiveadvantage and foreign policy analysis, will describe the direction of the object ofanalysis .This study will focus on explaining the Japanese strategy in maintainingrobot dominance in China's. As well as to see the development of the Japaneserobots in the world. Japan assessing the economic relationship with China mustbe maintained so that the robot can survive in China. This study will answer howJapan tried to maintain robot dominance in China's.Japan seeks to implement a strategy of Japan value and western quality,iron triangle relationship, rikkoku Gijutsu policy, and international level robotfestival. Effort in the Japanese did have a great opportunity to make the country'seconomy increased especially in the field of advanced technology. It is Japan'sforeign policy strategy to meet the national interest and increase dominance inChina's exports robot.Keywords : Strategy Japan , Japanese robot , Japanese and Chinese Economy